Public Health and Online MICE Technology During the COVID-19 Pandemic: The Role of Health Beliefs and Technology Innovation - Yao, Jinge; Pang, Qiwei; Zhang, Binyuan; Wang, Lu; Huang, Yiling (Frontiers in Public Health, 2021)
The traditional meetings, incentives, conferences, and exhibitions (MICE) industry has been hit hard by social distancing regulations introduced to combat the COVID-19 pandemic, with concerns about pandemic risks and personal hygiene increasing the demand for online MICE technology. With the introduction of innovative new technologies to the MICE industry, it is important to study the psychology of online MICE attendees, particularly the factors affecting their behavioral intention to adopt online MICE technology during the pandemic. This study investigates the attitudes toward attending online MICE since the start of the epidemic based on the health belief model (HBM) and innovation diffusion theory (IDT). A total of 439 valid questionnaires were collected in China and used for structural equation modeling. The results show that the perceived safety threat, the comparative advantage, trialability, and outcome expectations positively impact the attendees' attitudes. Moreover, this study finds that attitude completely mediates the impact of perceived safety threat, comparative advantages, trialability, and outcome expectation on behavioral intention to attend online MICE events. These findings theoretically enrich the understanding of online MICE technology, the HBM, and the IDT and offer managerial implications for MICE organizers and exhibitors.